DEFINE AND EMPOWER: Black Feminist Discourse in a Caribbean Context - Kennedy-Jude Providence (Caribbean Studies Students' Union, 2023)
In the global Feminist forum, many women and women-identifying voices are forgotten and subsequently omitted. Women of colour, specifically Black women, are often left out of discourses due to the troubled history of Feminism and its founders. In light of this, black women have frequently been forced to create narratives and discourses through art, music, resistance and scholarship. This discussion aims to highlight the progression of Feminism over the years, beginning with its troubled past and recognizing the potential for its future while incorporating discussions of the reclamation or emergence of Black Caribbean Feminism from the residual shackles of colonialism and the patriarchy.